Long-term evaluation of periodontal parameters and implant outcomes in periodontally compromised patients: a systematic review (2015)
Background: The aim of this systematic review is to evaluate the long-term outcomes of patients with periodontitis submitted to periodontal therapy/maintenance and implant placement. Methods: Studies reporting clinical and/or long-term implant outcomes from partially edentulous patients with periodontitis who were treated and followed periodontal maintenance for >5 years were considered eligible for the review. Screening of the articles, data extraction, and quality assessment were conducted independently and in duplicate. Results: Search of MEDLINE, EMBASE, and CENTRAL databases resulted in 959 papers, and of them 931 were excluded after title/abstract assessment. The full texts of 28 potentially eligible publications were screened, but only 10 studies met inclusion criteria. Most of the included studies (77.8%) presented a medium/high methodologic quality. The results demonstrated that patients with a diagnosis of periodontitis had satisfactory implant outcomes. Implant survival was high (92.1%) within studies reporting 10 years of follow-up. Parameters related to probing depth, clinical attachment level, and bone loss around teeth increased the occurrence of peri-implantitis and implant loss. Non-attendance to periodontal maintenance and smoking habits were also associated with less favorable implant outcomes. Conclusions: This systematic review confirmed that implant therapy can be successfully used in patients with a diagnosis of periodontitis who underwent proper therapy and regular periodontal maintenance. Residual pockets, nonattendance to the periodontal maintenance program, and smoking were considered to be negative factors for the long-term implant outcomes.